Report on professional attachment with Goh Ngiap Suan & Co. - Loh, Shan Li. (2008)
This report is prepared based on eight weeks of personal experience as an intern in Goh Ngiap Suan & Co. It focuses on the duties assigned, the knowledge and skills acquired, as well as my thoughts and reflections.